Gastric Function in Children with Oesophageal Atresia and Tracheoesophageal Fistula - Duvoisin, Gilles; Krishnan, Usha (Frontiers in Pediatrics, 2017)
Oesophageal atresia and tracheoesophageal fistula (OA-TOF) are a multifaceted condition which affect patients throughout their lives. Even though it is one of the most common gastrointestinal malformations, most of the current studies focus on gastro-oesophageal reflux disease, anastomotic strictures, and feeding difficulties. However, there is increasing evidence that a proportion of patients with OA-TOF also have abnormal gastric function. This review aims to provide a comprehensive understanding of studies of gastric function in patients with OA-TOF. The aetiology of this abnormality has been hypothesised to be congenital and/or acquired. Several modalities are currently available for the investigation of gastric function, each of them trying to answer specific clinical questions. This review summarises the studies which have looked at gastric function in the OA-TOF cohort with gastric emptying studies (gastric emptying scintigraphy and 13C octanoic breath test), gastric manometry, electrogastrography and oral glucose tolerance test. However, these modalities are limited due to poor age-specific normative values and heterogeneous methodologies used. The evaluation of symptoms in this cohort is crucial, modalities for abnormal gastric function are also described. With appropriate investigations and symptoms questionnaires, treatment strategies can be implemented to correct abnormal gastric function and thereby improve the outcomes and quality of life of patients with OA-TOF. This review highlights the need for large international multicentre collaborative studies and high-quality prospective randomised controlled trials to improve our understanding of gastric function in this cohort.